2010
DOI: 10.1086/652496
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Activated Transfected Killer Cells for Neutropenic Fungal Infections

Abstract: Background Invasive fungal infections cause considerable morbidity and mortality in neutropenic patients. White blood cell transfusions are a promising treatment for such infections, but technical barriers have prevented their widespread use. Methods To recapitulate white blood cell transfusions, we are developing a cell-based immunotherapy using a phagocytic cell line, HL-60. We sought to stably transfect HL-60 cells with a suicide trap (herpes simplex virus thymidine kinase), to enable purging of the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although neutrophil‐like cell lines are currently available, they originally derive from human leukemic samples, which may hamper safe clinical use. Lin et al have shown that HL‐60‐differentiated neutrophil‐like cells, named ATAK, improve overall outcome in a chemotherapy‐treated neutropenic mouse model challenged with Candida albicans and Aspergillus fumigatus [72]. Their effort to engineer a “suicide trap” within these cells points toward the significant safety concern of transplanting immortalized cells into patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although neutrophil‐like cell lines are currently available, they originally derive from human leukemic samples, which may hamper safe clinical use. Lin et al have shown that HL‐60‐differentiated neutrophil‐like cells, named ATAK, improve overall outcome in a chemotherapy‐treated neutropenic mouse model challenged with Candida albicans and Aspergillus fumigatus [72]. Their effort to engineer a “suicide trap” within these cells points toward the significant safety concern of transplanting immortalized cells into patients.…”
Section: Resultsmentioning
confidence: 99%
“…Antifungal therapy failured to manage the infection due to the presence of hyphae, the main feature of the fungus that allows it to penetrate blood vessels, and this prevents the penetration of antifungal agents into the fungus (Mehrad et al, ). Studies conducted have shown that neutrophils display potent anti‐ Aspergillus activity, exhibiting efficient migration to sites of fungal infection (Farowski et al, ; Lin et al, ; Lin, Ibrahim, Baquir, Palosaari, & Spellberg, ; Todeschini et al, ). It has been also found that posaconazole, a broad‐spectrum antifungal, accumulates in large concentrations in leukocytes, especially in neutrophils (Campoli et al, ; Conte Jr. et al, ; Hof, ).…”
Section: Neutrophil‐targeted Drug Delivery In Respiratory Diseasesmentioning
confidence: 99%
“…A variety of animal models demonstrate efficient neutrophil chemotaxis with rapid extravasation to the site of fungal infections. [48][49][50][51] To correct deep neutropenia multiple trials using granulocyte transfusions have been attempted. Despite these efforts, the results have been largely disappointing without a clear signal of protection.…”
Section: Neutrophilsmentioning
confidence: 99%